4CPS-014 Clinical and assisted impact of ischaemic ictus in patients treated with oral anticoagulants. (24th March 2020) - Ruiz, J; Juanes Borrego, A; López Vinardell, L; Plaza Diaz, A; Puig Campmany, M; Mangues Bafalluy, MA
Abstract : Background and importance: Anticoagulants are one of the therapeutic groups most frequently involved in drug related problems in the emergency services. However, the therapeutic management and the impact of assistance for those anticoagulated patients who suffer a stroke episode are not known. Aim and objectives: To describe the therapeutic management and healthcare impact of patients with atrial fibrillation treated with oral anticoagulants (OAT) admitted in an emergency services due to a thromboembolic stroke. Material and methods: This was a retrospective observational study. Adult patients (>18 years old) with atrial fibrillation receiving treatment with OAT admitted for cardioembolic stroke were included (January 2017–June 2019). Anticoagulant dosing prior to the stroke episode was evaluated. The modified Rankin Scale (mRS) score and National Institutes of Health Stroke Scale (NIHSS) score at admission and discharge, anticoagulant treatment prescribed after the episode and number of consultations to the emergency department in the year after hospital discharge were recorded. Results: Thirty-two patients were included (mean Age 75.2 (11.8) years): 22 (68.7%) were treated with vitamin K antagonists (VKA) and 10 (31.2%) with direct oral anticoagulants (DOACs). Eleven (34.4%) patients had a mRS score of 0 prior to the episode, 6 (18.8%) had a score of 1, 13 (40.6%) a score of 2 and 2 (6.2%) a score >2. The median score on the NIHSS scale at admission was 14 points (IQR 10–20) and 1 (0–7) point at discharge. Five (15.6%) patients died during hospitalisation. Among patients receiving VKA treatment, 13 (59.1%) had an international normalised ratio of <2 points at admission. Regarding DOACs, 5 (50.0%) patients had lower doses than the dose recommended. Of the 27 patients discharged, 17 (62.9%) changed their anticoagulation treatment at discharge, 2 (7.4%) increased their previous dose and in 2 (7.4%) patients the anticoagulant therapy was withdrawn. Fifteen (55.5%) patients presented again to the emergency department during the year after discharge: 7 (46.6%) were events directly related to anticoagulant therapy. Conclusion and relevance: A significant percentage of patients treated with DOACs suffering from stroke were under dosed. Consultations after discharge were frequent in this group of patients. Our results open the door to the design of multicentre studies that will allow us to verify the best anticoagulation strategies in this group of patients. References and/or acknowledgements: No conflict of interest.